Prevalence and associated risk factors for mental health problems among young adults in Fiji Island during COVID-19: a cross-sectional study - Khan, Mohammad G. M.; Patwary, Muhammad Mainuddin; Mamum, Kabir A.; Chand, Aneesh A.; Edward, Kaamil; Prasad, Kushal A.; Browning, Matthew H. E. M.; Prasad, Chaandvi; Shuvo, Faysal Kabir (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic has had a significant impact on mental health globally. To understand the impact of the pandemic on mental health in Fiji, this study aimed to investigate the prevalence of anxiety disorder and depression among the young adults. Method An online survey was conducted to assess the prevalence of anxiety disorder and depression among the general population in Suva, Fiji during the COVID-19 pandemic. A total of 1,119 Fiji adults participated in the study. The study was conducted between May 20 to June 30, 2022, using a snowball sampling via social media platforms. The Generalized Anxiety Disorder (GAD-7) and Patient Health Questionnaire (PHQ-9) scales were used to measure anxiety and depression, respectively. The COVID-19 related stressors was evaluated using the adapted SARS stressors assessment. Univariate and multivariate logistic regression analysis was performed to determine the factors influencing mental health among respondents. Results The result shows that a significant portion of individuals experienced each of the stressors, with the highest prevalence seen for hearing information about the severity of COVID-19. The prevalence of anxiety and depression was found to be 45% and 49%, respectively. Being female, having pre-existing illness and COVID-19 stressors were a risk factor to develop anxiety and depression. On the other hand, employed individuals and having high BMI was a protective factor against developing depression during COVID-19 lockdown. Conclusion These findings highlight the importance of addressing the mental health needs of the Fijian population during the COVID-19 pandemic and beyond.